Experimental Investigation of a Hybrid Device Combining a Wave Energy Converter and a Floating Breakwater in a Wave Flume Equipped with a Controllable Actuator - Luca Martinelli; Giulio Capovilla; Matteo Volpato; Piero Ruol; Chiara Favaretto; Eva Loukogeorgaki; Mauro Andriollo (Energies, 2023)
This paper presents a hydrodynamic investigation carried out on the “Wave Attenuator” device, which is a new type of floating breakwater anchored with piles and equipped with a linear Power Take Off (PTO) mechanism, which is typical for wave energy converters. The device is tested in the wave flume, under regular waves, in slightly non-linear conditions. The PTO mechanism, that restrains one of the two degrees of freedom, is simulated through an actuator and a programmable logic controller with preassigned strategy. The paper presents the system identification procedure followed in the laboratory, supported by a numerical investigation essential to set up a credible control strategy aiming at maximizing the wave energy harvesting. The maximum power conversion efficiency under the optimal PTO control strategy is found: it is of order 50–70% when the incident wave frequency is lower than the resonance one, and only of order 20% for higher frequencies. This type of experimental investigation is essential to evaluate the actual efficiency limitations imposed by device geometry.